Osebnostna struktura v zgodnjem in srednjem mladostništvu, kot jo (samo)zaznavajo mladostniki, njihovi sošolci in mame - Smrtnik Vitulić, Helena (Psihološka obzorja (Ljubljana), 2009)
The study investigated the personality structure of adolescents in early and middle adolescence periods. The research was conducted longitudinally and was based on a multiple-informant approach. Target adolescents, their classmates and mothers (self)assessed the adolescents' perosnality characteristics separately by using the Inventory of child individual difference (ICID). At the first measurement, the target group were 219 adolescents (M=14;7 years) attending the eight-grades of elementary schools in different regions of Slovenia. The second measurement was performed two years later, when most of the respondents attende the second grade of secondary schools (the attrition of the sample by 14%). Following the inspection of the resluts of component analyses conducted by the 15 ICID scales a four component solution was retained across the three groups of informants. With regard to adolescent self-report and mothers' report, four components were suggested at both times of measurement: extraversion, conscientiousness, emotional instability and disagreeableness, whereas the four components by ratings of peers yielded a combined extraversion - emotional stability, conscientiousness, amiability and disagreeableness. At both measurements the intellect/openness, presumably capturing the intelligence and open to experience marker scales, was not identified as an independent component. In self- and peer reports the intelligence scale loaded for the conscientiousness component, whereas according to mothers' assessments it correlated negatively with the emotional instability component. The open to experience scale loaded for the extraversion component (self-report and report by mothers) and to the extraversion - emotional stability component (peer assessments), respectively.
Keywords: osebnostne lastnosti; struktura osebnosti; mladostništvo; model velikih pet; petfaktorski model osebnosti; psihologija osebnosti